2002
DOI: 10.1021/je010252v
|View full text |Cite
|
Sign up to set email alerts
|

Excess Molar Enthalpies of N,N-Dimethylformamide + Alkan-1-ols (C1−C6) at 298.15 K

Abstract: Excess molar enthalpies, , for the binary systems N,N-dimethylformamide + methanol, + ethanol, + propan-1-ol, + butan-1-ol, + pentan-1-ol, and + hexane-1-ol have been measured at 298.15 K and atmospheric pressure with a Parr 1455 solution calorimeter. While the excess molar enthalpies are negative for the methanol mixture, those for ethanol, propan-1-ol, butan-1-ol, pentan-1-ol, and hexan-1-ol mixtures are positive over the entire range of composition of N,N-dimethylformamide. The values at around x ≈ 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…This paper is a continuation of our earlier work [1][2][3][4][5]. The number of studies on thermodynamic properties of ternary mixtures has increased in recent years due to industrial applications and the theoretical interest in studying the nature of molecular interaction and packing phenomena in ternary mixtures.…”
Section: Introductionmentioning
confidence: 78%
“…This paper is a continuation of our earlier work [1][2][3][4][5]. The number of studies on thermodynamic properties of ternary mixtures has increased in recent years due to industrial applications and the theoretical interest in studying the nature of molecular interaction and packing phenomena in ternary mixtures.…”
Section: Introductionmentioning
confidence: 78%
“…From a theoretical point of view, mixtures containing hydroxyethers are very important, not only because of their selfassociation but also due to the strong intramolecular effects which is produced by the presence of -O-and -OH groups in the same molecule [3]. Physicochemical and thermodynamic investigations play an important role in helping to understand the nature and the extent of the patterns of molecular aggregation that exist in binary liquid mixtures and their sensitivities to variations in composition and the molecular structure of the pure components [4,5]. The experimental data of excess thermodynamic properties of liquid mixtures provide useful information about molecular interactions and can be used to test thermodynamic models [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the partial molar quantity Ea 1 (x1) related to DMF regularly decreases from a maximum (about 16 kJ mol -1 ) to tend to a local minimum (about 4.5 kJ mol ) at (x1 = 0.55), then increases to reach the value of pure DMF (around 9.28 kJ mol -1 ). This behaviour supposes that at high dilution of DMF, the introduction of DMF into EtOH promotes the hetero-asso- ciation formation through multiple hydrogen bounds between the polar groups of unlike molecules till the molar fraction x1 ≈ 016 = 1/6 (1DMF:5EtOH) where there is a beginning of structure changing of EtOH [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Thermodynamic Charactersmentioning
confidence: 99%